White Grape Pomace Effect on Laying Hens’ Productivity, Egg Quality Traits, and Antioxidant Capacity Under Normal, Heat, and Cold Thermal Conditions - Gabriela Maria Cornescu; Tatiana Dumitra Panaite; Ana Elena Cișmileanu; Mihaela Sărăcilă; Arabela Elena Untea; Iulia Varzaru (Agriculture)
This study investigated the effect of white grape pomace (WGP) via a 6% level dietary supplementation on laying hens exposed to varying thermal stress conditions. The experiment was designed as a 2 × 3 factorial study, incorporating two dietary treatments (C and E) and three different thermal conditions: normal (NT: 22 °C), high stress (HST: 35 °C), and low stress (LST: 10 °C). Feed and water were provided ad libitum throughout the experiment. Results showed that the inclusion of 6% WGP in laying hens’ diet did not demonstrate beneficial effects under HST conditions, but under LST conditions, the WGP showed higher final body weight (1849.38 g) compared to both groups from the HST conditions (C 1599.40 g and WGP 1592.59 g), and the AEW (average egg weight) was highly significantly higher (p = 0.0001) compared to the C or NT groups (both groups, 2nd week), and the HST conditions (both groups, 2nd, 4th, and 6th weeks). HDEP (hen-day egg production) registered highly significant values (p = 0.0001) for the WGP group under HST conditions compared to HST conditions (both groups, 4th and 6th weeks). The whole egg weight was highly significant (p = 0.0001) for the WGP group under LTS conditions compared to the C group and to HST conditions (both groups, 2nd week and 6th week). The yolk weight parameter registered highly significant (p = 0.0001) values for the WGP group under LTS conditions compared to the C group and HST conditions (both groups, 2nd week; C group, 4th week; both groups 6th week) and the NT conditions (C group, 2nd week). Our study indicates that dietary supplementation with 6% white grape pomace (WGP) has potential benefits in LST conditions but limited efficacy under HST conditions. Further research is needed to explore the mechanisms and optimal inclusion levels of WGP in diets for laying hens exposed to different temperatures, especially in HST conditions.